2018
DOI: 10.1007/s42321-018-0014-4
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the English Box: Constructing and Communicating Knowledge Through Translingual Practices in the Higher Education Classroom

Abstract: As part of the growing trend of internationalization in higher education, new forms of linguistic practices are recently emerging in diverse contexts. However, such practices are often obscured by English medium instruction (EMI) policies, neglecting the role of other languages, semiotic resources, and modalities in the construction and communication of knowledge. Building on an expanded framework of language policy, in this study I take a Btrans-^approach to reconceptualize the BE^in EMI. Specifically, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…Grounded on this interpretation, translanguaging thusly views the deployment of multimodal communicative resources such as, to name a few, posture, objects, visual cues, gestures, gazes, facial expressions, and even emojis in technological interactions as a natural and integral form of the dynamic flow of human communication. This is well exemplified in Chang's (2019) study which demonstrated how 18 lecturers in a Taiwanese EMI university "used different languages (e.g., English, Chinese, and Taiwanese), modalities (e.g., PowerPoint slide, videos, and textbooks), and semiotic resources (e.g., numbers) in the process of teaching and learning" (p. 36). The following section moves to shed light on the potential of tanslanguaging as an educational practice in the TESOL field.…”
Section: Understanding Translanguagingmentioning
confidence: 84%
“…Grounded on this interpretation, translanguaging thusly views the deployment of multimodal communicative resources such as, to name a few, posture, objects, visual cues, gestures, gazes, facial expressions, and even emojis in technological interactions as a natural and integral form of the dynamic flow of human communication. This is well exemplified in Chang's (2019) study which demonstrated how 18 lecturers in a Taiwanese EMI university "used different languages (e.g., English, Chinese, and Taiwanese), modalities (e.g., PowerPoint slide, videos, and textbooks), and semiotic resources (e.g., numbers) in the process of teaching and learning" (p. 36). The following section moves to shed light on the potential of tanslanguaging as an educational practice in the TESOL field.…”
Section: Understanding Translanguagingmentioning
confidence: 84%
“…However, although participants reported translanguaging practices, they did not appear to embrace a translanguaging ideology (Chang, 2019). English-only was desired by students to create 'immersion' (see Sahan & Rose, 2021), and by teachers because it is what they are 'paid' to do (see Kirkpatrick, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The application of EMI in the teaching and learning process in non-Englishspeaking countries is still an intriguing topic nowadays (Chang, 2019;Goodman, 2014;Salahshour et al, 2013;Yuan et al, 2020). Although using English as the target language continues to cause many challenges in various nations, the policy of applying EMI is still seen to be able to greatly motivate both educators and students to grasp English literacy (Chang, 2019;Floris, 2014).…”
Section: Introductionmentioning
confidence: 99%